Viewing Citation Analysis Through the Lens of Citation Justice - Smith, Linda C. (KULA)

(untitled) (University of Victoria Libraries, 2026)
Given the recent growing emphasis on citation justice and related concepts, this paper examines "Citation Analysis," published in Library Trends in 1981, and revisits it through the lens of citation justice. Overarching questions include: How can citation analysis be more just? How can research evaluation go beyond citation analysis to be more just? Sections include a discussion of the concept of citation justice, applications of citation analysis with particular emphasis on evaluative bibliometrics, characterization of assumptions underlying citation analysis, identification of problems posed in dealing with citation data, and an outline of possible approaches to achieving citation justice. Several different entities and actions are discussed with the goal of working toward citation justice. These include author roles, pedagogical approaches, resource compilation, editor and reviewer roles, publisher roles, advocacy, recommendations for research evaluation reform, and higher education institutional roles. Viewing citation analysis through the lens of citation justice reveals significant limitations in citation analysis and suggests ways to correct them–both to ensure that more diverse scholars are part of the scholarly conversation that underlies citation analysis and to encourage approaches to research evaluation that are not dependent solely on citation counts.